1986
DOI: 10.1159/000183653
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of 24,25-Dihydroxyvitamin D Levels in Patients Treated with Continuous Ambulatory Peritoneal Dialysis

Abstract: We measured 24,25-dihydroxyvitamin D [24,25(OH)2D] levels in patients treated with chronic ambulatory peritoneal dialysis (CAPD), before and after receiving vitamin D2 or 1α-hydroxyvitamin D3 (1α-OH-D3). Vitamin D2 administration led to an increase in 25-hydroxyvitamin D (25-OH-D) and a concomitant rise in 24,25(OH)2D. No change was observed in 1,25-dihydroxyvitamin D [1,25(OH)2D]. Administration of 1α-OH-D3 resulted in an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

1987
1987
2008
2008

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 8 publications
1
5
0
Order By: Relevance
“…25‐OH‐D 3 and 1,25(OH) 2 D 3 fractions were separated by the Sep‐Pak separation procedure using C‐18 and silica columns 25. The 25‐OH‐D 3 fraction was submitted to a competitive protein binding assay using diluted rachitic rat serum as the binding protein 26. The 1,25(OH) 2 D 3 fraction was determined quantitatively by a vitamin D receptor (VDR) binding assay27 using calf thymus VDR as the ligand binder (Nichols Co.).…”
Section: Methodsmentioning
confidence: 99%
“…25‐OH‐D 3 and 1,25(OH) 2 D 3 fractions were separated by the Sep‐Pak separation procedure using C‐18 and silica columns 25. The 25‐OH‐D 3 fraction was submitted to a competitive protein binding assay using diluted rachitic rat serum as the binding protein 26. The 1,25(OH) 2 D 3 fraction was determined quantitatively by a vitamin D receptor (VDR) binding assay27 using calf thymus VDR as the ligand binder (Nichols Co.).…”
Section: Methodsmentioning
confidence: 99%
“…25-(OH)D and 1,25-(OH) 2 D fractions were separated by a Sep-Pak (Waters, Milford, MA) separation procedure using C-18 and silica columns (33). The 25-(OH)D fraction was submitted to a competitive protein-binding assay using diluted rachitic rat serum as the binding protein (34). Quantification of the 1,25-(OH) 2 …”
Section: Serum 25(oh)d and 125(oh) 2 D Determinationmentioning
confidence: 99%
“…Shany et al [24] demonstrated that CAPD patients with kidneys in situ appear to be able to produce an adequate serum level of 1,25 and 24,25(OH)3D3 if administered 1-a-OH-D alone. Salusky et al [25] suggest high-dose l,25(OH)2D3 for control of renal osteodystrophy, and Delmez et al [26] suggest intraperitoneal dialysate supplemented with 4.0 mEq/1 cal cium and 0.5 ug l,25(OH)2D3.…”
Section: Discussionmentioning
confidence: 99%